Ghostmapping: A Public Lecture Series - Kansas State University, K-State First (Kansas State University. K-State First., 2014)
This poster advertised Ghostmapping: A Public Lecture Series. Four people from the Kansas State University community gave lectures related to issues raised in the Steven Johnson’s book, "The Ghost Map: The Story of London's Most Terrifying Epidemic -- and How It Changed Science, Cities, and the Modern World."
Keywords: Ghost Map, The; Events; Common reading program; Engagement; Mapping; Faculty lecture; Promotional materials